Molecular Mechanism of Cholerae Toxin (ctx) in Causing Diarrhea - Praja, Rian Kusuma Arinta; Rosalina, Reny (Universitas Hang Tuah, 2018)
Vibrio cholerae is one of the pathogenic bacteria transmitted through contaminated food, especially seafood and contaminated beverages. V. cholerae produces cholerae toxin (ctx) which is encoded by the ctx gene located within its chromosome. This toxin has been recognized as one of the toxins responsible for cholera outbreaks. The mechanism of ctx gene expression is induced by environmental signals such as pH, osmolarity, temperature, bile, amino acids, and CO2. These signals will be a positive transcriptional factor to the ToxR gene that regulates the biogenesis of cholerae toxin. After cholerae toxin has been successfully expressed, V. cholerae uses a type II secretion (T2S) pathway to deliver cholerae toxin to the extracellular environment. Cholerae toxin consists of A and B subunits. The B subunit plays a role in attaching to the receptor Manosialosyl Ganglioside (GM1 ganglioside) and the A subunit plays a role in catalyzing ADP-ribosylation of Gs (stimulatory) proteins and turning them into active condition. The Gs proteins will convert the inactive adenilate cyclase (AC) into active AC. The increase of AC activity will increase the cyclic adenosine 3'5'-monophosphate (cAMP) concentration along the cell membrane. The cAMP then causes the active secretion of sodium (Na+), chloride (Cl-), potassium (K+), bicarbonate (HCO3-), and water (H2O) out of the cell into the intestinal lumen, resulting in large fluid losses and electrolyte imbalances. Keywords: Vibrio cholerae, cholerae toxin (ctx), ToxR gene, type II secretion (T2S), GM1 ganglioside, adenilate cyclase.